Financial technology impact on stability of financial institutions - Stankevičienė, Jelena; Kabulova, Jelena (Technological and Economic Development of Economy, 2022)
It is a controversial question whether financial technology makes financial institutions vulnerable (instable). This research is based on the analysis of financial institutions from 37 countries. Authors use regulatory sandboxes that are introduced in countries as an external FinTech shock to examine the impact of financial technology on financial institution stability. Some observations can be drawn: 1) if market characteristics are not considered, then there is no effect on the financial institution vulnerability linked to the shock of FinTech innovation; 2) development of FinTech in developed countries can reduce (or increase) the vulnerability (instability) of financial markets; 3) FinTech impacts the vulnerability (instability) of financial institutions through the profitability.Nevertheless, these indicators do not consider the complex multidimensional essence of FinTech. This article summarises how FinTech and developed financial institutions and the financial sector are in terms of their depth, access, and efficiency. The article offers a valuable analytical means of developing FinTech impact on financial stability for researchers and policymakers.